2016
DOI: 10.1289/ehp129
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis in Agricultural Health Study Spouses: Associations with Pesticides and Other Farm Exposures

Abstract: Background:Farming has been associated with rheumatoid arthritis (RA), but the role of pesticides is not known.Objectives:We examined associations between RA and pesticides or other agricultural exposures among female spouses of licensed pesticide applicators in the Agricultural Health Study.Methods:Women were enrolled between 1993 and 1997 and followed through 2010. Cases (n = 275 total, 132 incident), confirmed by a physician or by self-reported use of disease modifying antirheumatic drugs, were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 51 publications
(70 reference statements)
6
40
2
7
Order By: Relevance
“…The association of chemical fertilisers with RA in the present study corroborates our earlier findings in female spouses 13. A previous case-control study also reported an association with fertilisers and RA in men, but did not specify the type of fertiliser 12.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The association of chemical fertilisers with RA in the present study corroborates our earlier findings in female spouses 13. A previous case-control study also reported an association with fertilisers and RA in men, but did not specify the type of fertiliser 12.…”
Section: Discussionsupporting
confidence: 91%
“…The observed associations of RA with solvents and painting confirm results from our previous analysis of RA in female spouses 13. Organic solvents have been related to other types of autoimmune diseases, but evidence is limited for RA 32.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Early research in the Agricultural Health Study cohort showed no association of RA in women reporting use of DDT, but the study included only 135 cases (mostly prevalent) (44). Subsequent analyses in the Agricultural Health Study showed lifetime DDT use was associated with incident RA, primarily in women who had grown up on a farm (45). Women with a childhoodfarm history may have had earlier, longer, or more frequent pesticide exposures.…”
Section: Discussionmentioning
confidence: 99%